2008
DOI: 10.1161/strokeaha.108.514356
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death and Stroke After Carotid Angioplasty and Stenting

Abstract: Background and Purpose-Little is known about the significance of patient characteristics, clinical indications, and technical details on the risk of carotid angioplasty and stenting (CAS). The purpose of this study was to test these parameters as to their predictive value for the peri-interventional risk of CAS. Methods-Pro-CAS is a prospective, multicenter registry of CAS. Logistic regression analysis of possible predictive factors was performed on 5341 interventions that had been entered by 25 clinical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 28 publications
6
94
1
5
Order By: Relevance
“…This confirms previous reports indicating a learning curve for carotid stenting [21][22][23][24], and is in keeping with multiple reports of the same phenomenon in CEA and other endovascular therapies [25][26][27].…”
Section: Increase In Physician Volume and Experiencesupporting
confidence: 92%
“…This confirms previous reports indicating a learning curve for carotid stenting [21][22][23][24], and is in keeping with multiple reports of the same phenomenon in CEA and other endovascular therapies [25][26][27].…”
Section: Increase In Physician Volume and Experiencesupporting
confidence: 92%
“…15 In their statistical subgroup analysis, sex also was not an independent predictor of peri-interventional stroke or death. 15 Theiss et al reported a periprocedural stroke or death rate in 3.5% of men and 3.0% of women undergoing CAS (P = 0.42), which corresponds nicely to our peri-interventional death or stroke rates of 3.4% in women and 3.0% in men treated with CAS (P = 0.47) in a comparable population in clinical practice. In addition, several randomized clinical trials (SPACE, CREST, International Carotid Stenting Study [ICSS]) comparing CAS to CEA also did not show a significant impact of sex on the outcome of patients undergoing CAS.…”
Section: Outcome In Women Vs Men Undergoing Carotid Artery Stentingmentioning
confidence: 91%
“…The risk for procedure-related complications and clinical outcome in CAS may depend on various factors, for example the center experience, the patient's age, and previous intervention on the vessel. 15 Knowing these risk factors may lower the risk for periprocedural complications in the future and make CAS an even safer procedure. A possible impact of the patient's sex on the outcome of the CAS in clinical practice has not been investigated in detail, and only little information about this topic is available so far.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies reported the relationship using UK data sources 11,15,16,18,19,21 Nine studies [11][12][13][14][15][16][17][20][21][22] analysis of data collected as part of an administrative database.…”
Section: Resultsmentioning
confidence: 99%
“…Kuehnl et al 14 conducted a range of adjusted and unadjusted analyses and found no association (Table 5). Two smaller studies 17,22 found evidence of a statistically significant relationship between CAS volume and combined mortality and stroke in unadjusted analyses. These positive correlations were not replicated in multi-variate analysis adjusted for temporal trends, patient and operative factors and cumulative institutional experience (distinct from a caseload count in a fixed period) 22 .…”
Section: Cas and Combined Stroke/death: Hospital Volumementioning
confidence: 99%